Faktor-Faktor Yang Berhubungan Dengan Kejadian Insomnia Pada Mahasiswa FKM UHO Tahun 2025 - Raqhil Caesario Sanggo; Jafriati; Hariati Lestari (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
Insomnia is the inability or difficulty sleeping both in terms of quantity and quality. Complaints for insomnia sufferers are characterized by complaints of difficulty sleeping, feeling short of sleep, sleeping with frightening dreams, and complaints of disturbed health. The causes of insomnia come from internal factors (intrinsic), namely: anxiety, stress, motivation and age while external factors (extrinsic), namely: use of drugs, general medical disorders, environmental and lifestyle factors such as smoking, using gadgets without time, irregular physical activity, and consuming caffeinated drinks. This study aims to determine what factors are related to the occurrence of insomnia in students of the Faculty of Public Health, Halu Oleo University in 2025. The research method used in this study is an analytical research method with a cross-sectional approach. The population in this study was 766 students of the Faculty of Public Health, Halu Oleo University, class of 2021 and 2022. The number of samples in this study was 256 students. The sampling technique used in this study was probability sampling using stratified random sampling technique. The results of this study indicate that there is a relationship between the duration of gadget use (0.000), physical activity (0.005), stress level (0.000), and anxiety level (0.000) with the incidence of insomnia, and there is no relationship between family support (1.000) with the incidence of insomnia in students of the Faculty of Public Health, Halu Oleo University in 2025. It is hoped that students will pay more attention to their lifestyle because a healthy lifestyle is the key to achieving a prosperous and disease-free life.